Ultrafast Probe of Carrier Diffusion and Nongeminate Processes in a Single CdSSe Nanowire. (12th March 2015) - Eldridge, Peter S.; Blake, Jolie C.; Gundlach, Lars
Abstract : We measure ultrafast carrier dynamics in a single CdSSe nanowire at different excitation fluences using an ultrafast Kerr-gated microscope. The time-resolved emission exhibits a dependence on excitation fluence, with the onset of the emission varying on the picosecond time scale with increasing laser power. By fitting the emission to a model for amplified spontaneous emission (ASE), we are able to extract the nonradiative carrier recombination lifetime and nongeminate recombination constant. The extracted nongeminate recombination constant suggests that our measurement technique allows the access to the nondiffusion limited recombination regime in nanowires with low carrier mobility.